THE POLARITIES OF MAGNETIC STARS - POVEDA, ARCADIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1956)
The determination of polarities of magnetic stars is discussed in terms of the classical Zeeman effect, the design of the analyzer for polarized light used, and the appearance of the spectrograms. Is is shown that by a simple inspection of the spectrogram
BOL OBS TONAN TACUB
Keywords: POLARITIES, MAGNETIC, STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS